Analysis of Transfer Funds on Regional Expenditure of North Sulawesi Provincial Government Before and During Covid-19 Pandemic - Anugrah Alvionitha Tana; Lintje Kalangi; Heince R. N. Wokas (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This research addresses the dependency of Regional Governments, particularly North Sulawesi Provincial Government, on Transfer Funds for regional expenditures, with a focus on the changes brought about by the Covid-19 pandemic. The study aims to analyze the allocation process of Transfer Funds on regional expenditure before and during the pandemic. Design/methodology/approach: Utilizing a qualitative case study approach, this research employs the Miles and Huberman Model for analysis. The study investigates how the North Sulawesi Provincial Government adapted its budget allocation strategy in response to the Covid-19 pandemic, with specific attention to the allocation of Transfer Funds. Research Findings: The study reveals shifts in the focus of regional expenditure, emphasizing Covid-19 handling during the pandemic compared to the pre-pandemic period when expenditures were allocated based on the Governor's vision and mission. Limited fiscal space led to a more selective budget allocation by the Regional Government Budget Team. Efforts to address budget constraints included refocusing and reallocating funds, supervision and assistance to regional apparatus, and regular evaluation of Transfer Funds. Theoretical Contribution/Originality: This research contributes by highlighting the dynamic changes in regional expenditure allocation, specifically addressing the impact of the Covid-19 pandemic. It provides insights into adaptive fiscal strategies employed by regional governments during crises. Research limitation and implication: Limitations include the focus on a specific region and the qualitative nature of the study. Future research may explore diverse regions and incorporate quantitative methods for a broader analysis. The findings suggest that regional governments need adaptive fiscal policies during crises. Policymakers can learn from North Sulawesi's experience, emphasizing the importance of flexibility and strategic reallocation of funds to address urgent priorities during emergencies.